2008
DOI: 10.1093/carcin/bgn044
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional CHEK2 mutations are associated with a decreased risk of lung and laryngeal cancers

Abstract: Mutations in the CHEK2 gene have been associated with increased risks of breast, prostate and colon cancer. In contrast, a previous report suggests that individuals with the I157T missense variant of the CHEK2 gene might be at decreased risk of lung cancer and upper aero-digestive cancers. To confirm this hypothesis, we genotyped 895 cases of lung cancer, 430 cases of laryngeal cancer and 6391 controls from Poland for four founder alleles in the CHEK2 gene, each of which has been associated with an increased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…Other variants in CHEK2 have been associated with lung cancer risk, but a possible association of 1100delC with lung cancer risk had never been investigated before. [26][27][28][29][30][31] Thus, we examined whether the 1100delC variant is associated with lung cancer risk by investigating a prevalent cohort of 457 lung cancer patients. Of these, 449 were homozygous wild type and 4 were heterozygous for the 1100delC mutation; no 1100delC homozygous patients were found (genotyping failed repeatedly for the remaining four patients).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other variants in CHEK2 have been associated with lung cancer risk, but a possible association of 1100delC with lung cancer risk had never been investigated before. [26][27][28][29][30][31] Thus, we examined whether the 1100delC variant is associated with lung cancer risk by investigating a prevalent cohort of 457 lung cancer patients. Of these, 449 were homozygous wild type and 4 were heterozygous for the 1100delC mutation; no 1100delC homozygous patients were found (genotyping failed repeatedly for the remaining four patients).…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25] Other variants in CHEK2 have been associated with lung cancer, but a possible association of 1100delC with lung cancer has never been investigated. [26][27][28][29][30][31] Homozygosity for 1100delC is expected to be rare, and until recently, there had only been two reports on homozygous carriers, a male who developed colon cancer at age 52 years 32 and a female who developed bilateral breast cancer at ages 47 and 61 years and uterine sarcoma at age 58 years. 33 Recently, Adank et al 34 reported 12 homozygous 1100delC mutation carriers from 8 breast cancer families from the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…30 The 2 other reported mutations, Ile157Thr and 1100delC, found in a total of 4 families suggestive of LFS 28,29 were subsequently shown to be polymorphisms, whose allele frequency has been, respectively, estimated to be 0.12% to 1.4% and 2.4% in European populations and which confer an increased risk for breast, prostate, and thyroid cancer. [31][32][33] These data argue against any major involvement of CHEK2 in LFS. A linkage to chromosome 1q23 was reported in a LFS family, 34 but the implication of a second locus in LFS remains to be confirmed.…”
Section: The Role Of Other Genes In Lfsmentioning
confidence: 99%
“…They are located upstream of MMPs in cell signaling pathways. The term ''upstream cancer-progression determinants'' (UCPDs, for brevity) will be used for them in this text.A very large number of proteins determine invasiveness and other cancer progression traits (Uchiyama et al, 1996;Twal et al, 2001;Wong and Gumbiner, 2003;Zheng et al, 2003 (Walsh and King, 2007;Cybulski et al, 2008). In order to begin the identification of a cell signaling pathway between two factors, it is essential to have detected first a pathway link between them.…”
mentioning
confidence: 99%